Unexpected vulnerability of Enterococcus faecium to polymyxin B under anaerobic condition - Yongjun Son; Bitnara Kim; Pureun Kim; Jihyeon Min; Yerim Park; Jihye Yang; Wonjae Kim; Masanori Toyofuku; Woojun Park (Gut Microbes)
Gram-positive Enterococcus faecium exhibited higher susceptibility (>4-fold) to polymyxin B (PMB), the canonical antimicrobial peptide against Gram-negative bacteria, under anaerobic condition than aerobic condition. Anaerobically grown E. faecium exhibited high vulnerability to PMB, leading to alteration of cell surface and morphology, as observed based on their high dansyl-PMB affinity (>2.9-fold), a proportion (>8.5-fold) of propidium iodide-stained cells, and observation of scanning electron microscopy results. Interestingly, our transcriptomic and chemical analyses revealed that enterocin B, produced anaerobically, imposes a burden on the cellular envelope when cells are exposed to PMB. This scenario was also supported by PMB susceptibility tests and killing curves, which showed that ΔentB knockout mutant cells were more resistant to PMB (32 µg/mL) compared to wild-type cells (4 µg/mL) under anaerobic condition. Fluorescent D-amino acid and BOCILLIN™-fluorescent profiling of transpeptidase activities in ΔentB mutant cells under anaerobic condition revealed similar levels of activity to those observed in WT cells under aerobic condition. The high level of secreted bacteriocins in WT under anaerobic condition likely led to significant membrane depolarization and loosening of the peptidoglycan layer, making the cells more permeable to PMB. Overall, our findings suggest that anaerobically produced bacteriocins, in conjunction with PMB, contribute to the killing of E. faecium by destabilizing its cell envelope.